Persepsi Orang Tua Terhadap Penggunaan Smartphone Pada Anak Di TK Negeri Pembina 02 Kampar - Eriya Oktavia; Amin Yusi Nur Sa’ida; Yenda Puspita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The advancement of information technology has had a significant impact on daily life, including on early childhood. The use of smartphones is no longer limited to adults but has also become prevalent among kindergarten-aged children a period known as the golden age in child development. This phenomenon has generated various perceptions among parents, ranging from viewing smartphones as educational tools to concerns about negative effects such as addiction, health issues, and reduced social interaction. This study aims to describe parents’ perceptions of smartphone use among children at TK Negeri Pembina 02 Kampar. The research used a descriptive qualitative method, with data collected through questionnaires, observation, and documentation. The findings show that 67.4% of respondents scored within the range of 17–20, indicating that parents’ perception of smartphone use is generally positive